2022
DOI: 10.1093/plphys/kiac582
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term responses of leaf day respiration to elevated atmospheric CO2

Abstract: Evaluating leaf day respiration rate (RL), which is believed differ from that in the dark (RDk), is essential for predicting global carbon cycles under climate change. Several studies have suggested that atmospheric CO2 impacts RL. However, the magnitude of such an impact and associated mechanisms remain uncertain. To explore the CO2 effect on RL, wheat (Triticum aestivum) and sunflower (Helianthus annuus) plants were grown under ambient (410 ppm) and elevated (820 ppm) CO2 mole fraction ([CO2]). RL was estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 67 publications
2
29
0
Order By: Relevance
“…Similar to previous results, including those from free-air CO 2 enrichment studies ( Ainsworth and Long 2005 ), Sun et al (2023) found a reduction in both leaf N and chlorophyl content under elevated (CO 2 ). Thus the concurrent reduction in R l and R d is linked to changes in N metabolism in leaves.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Similar to previous results, including those from free-air CO 2 enrichment studies ( Ainsworth and Long 2005 ), Sun et al (2023) found a reduction in both leaf N and chlorophyl content under elevated (CO 2 ). Thus the concurrent reduction in R l and R d is linked to changes in N metabolism in leaves.…”
supporting
confidence: 90%
“…However, the authors did not identify any significant change in the R l : R d ratio between each treatment. During a short-term change in (CO 2 ) during measurement, Sun et al (2023) found an increase in R l and the R l : R d ratio using the Kok and Kok-Phi method but not the Kok-Cc method, a discrepancy attributed to changes arising from differences in intercellular (CO 2 ). This indicates a tendency to underestimate R l and overestimate light inhibition under low light intensities using the Kok and Kok-Phi methods.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…The Kok method has large uncertainty concerning its two assumptions (Farquhar & Busch, 2017;Tcherkez et al, 2017a;Yin et al, 2020;Yin & Amthor, 2023), namely constant photochemical efficiency of photosystem II (Φ 2 ) and chloroplast CO 2 concentration (C c ) along the A-I inc curve. Both Φ 2 and C c have been shown to decline with increasing irradiance (Yin et al, 2011;Berghuijs et al, 2019;Sun et al, 2023). To address these issues, Yin et al (2011) suggested using measurements of Φ 2 via chlorophyll fluorescence to improve R L estimates (hereafter named 'Yin method').…”
Section: Introductionmentioning
confidence: 99%